Theoretical underpinnings and future research on academic stress in biological and educational perspectives - Wasis Wuyung Wisnu Brata; Hendra Susanto; Siti Zubaidah (Humanities & Social Sciences Communications)
Abstract Academic stress, which is a frequent experience for university students, has been demonstrated to have a considerable effect on their academic performance. However, the conceptual basis linking the biological mechanism of stress with educational outcomes remains fragmented. This systematic literature review seeks to synthesize current knowledge on the biological and educational perspectives of academic stress and its impact on student performance. Using the PRISMA framework, a comprehensive search was conducted in the Scopus database, yielding an initial pool of 4054 articles. After applying predefined inclusion and exclusion criteria focused on academic stress in university students, 31 articles were selected for detailed analysis. The review identifies four key theoretical foundations: the neurocognitive aspects of stress and performance, the neurophysiology of stress, epigenetic regulation of stress, and stress and genetic variations. Based on these insights, the study proposes three main directions for subsequent studies: enhancing the understanding of stress mechanisms, developing effective educational interventions, and employing interdisciplinary approaches in subsequent studies. These findings aim to provide a comprehensive framework for optimizing academic performance by deepening our understanding of the biological and educational dimensions of stress.